Concluding Athletic Careers: Post-Athletic Transitions in the Atlantic Coast Conference - Eric Sabin; Sarah Stokowski; Chris Corr; Brennan K. Berg; Michael Hutchinson (Journal of Applied Sports Management, 2023)
Due to the pervasiveness of athletic role engulfment and a salient athletic identity, collegiate athletes often experience difficulties upon conclusion of their competitive athletic career. Such engulfment and fixed athletic identity are detrimental to an athlete’s post-athletic transition. Given the role of athletic department institutional members (e.g., administrators, coaches, staff) in the formative development of collegiate athletes’ lives, athletic departments occupy an integral position to assist athletes in their post-athletic transition. To examine the practices currently implemented among National Collegiate Athletic Association (NCAA) athletic departments relative to holistic athlete development, semi-structured interviews were conducted with institutional members at nine (n = 9) Atlantic Coast Conference (ACC) athletic departments. Findings reveal thematic emphases on athletic department specific programming and intra-institutional collaboration to ensure a variety of resources and educational opportunities are consistently available to collegiate athletes during their college experience. Implications and actionable items are discussed in detail. Disclosure: This research was funded by the Atlantic Coast Conference – Center for Research in Intercollegiate Athletics (ACC-CRIA) Innovation Initiative Grant Program.
Keywords: post-athletic transition; role engulfment; athletic identity; NCAA